The phonetics of information structure in Yoloxóchitl Mixtec. (May 2018) - DiCanio, Christian; Benn, Joshua; Castillo García, Rey
Highlights: Prosodic marking of narrow, contrastive, and broad focus were examined in Yoloxóchitl Mixtec. Stressed syllable onsets were significantly lengthened under narrow and contrastive focus. Contrastive focus was produced with significant F 0 raising across tonal melodies. Narrow/contrastive focus involve F 0 range expansion and syntagmatic maintenance of lexical tone. Asymmetries in the locus of prosodic lengthening indirectly result in focal tonal enhancement. Abstract: Research on speech prosody has shown that higher-level phonological constituents can be examined directly via their influence on low level phonetic processes (Beckman & Edwards, 1990; Fougeron & Keating, 1997 ). Despite the strong tradition of research in this area, the existing work has focused mainly on languages which lack lexical tone. This contributes to the view that prosodic structures show little influence on tone, i.e. a language may either have lexical tone or lexical/phrasal stress, the latter of which fits into the prosodic hierarchy. The current paper examines prosodic focus in Yoloxóchitl Mixtec, an endangered Otomanguean language spoken in Mexico. Using experimental data from ten speakers in the field, we investigated how sentence position, stress, and focus type influenced the realization of F 0 and duration in different tonal melodies. The findings show that the tonal F 0 space was expanded and raised on words produced with contrastive focus, less on words produced with narrow focus, and least on words produced under broad, sentential focus. Focus-related lengthening asymmetrically affected stressed syllables in the language more than unstressed syllables. In stressed syllables, this resulted in an increase in tonal hyperarticulation.